Financial Planning Model at Internationally Accredited Islamic Universities: Integration of Islamic Principles - Ahmad Habibi Syahid; Burhanudin Hartono; Encu Suhartini; Nuroh Nuroh (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2025)
This research endeavors to address the critical need for a tailored Financial Planning Model designed specifically for internationally accredited higher education institutions (HEIs). In the context of escalating global competition and the heightened importance of financial sustainability in HEIs, the development of a robust financial planning framework becomes imperative. Through a synthesis of qualitative and quantitative methodologies, this study aims to identify and analyze the intricate financial dynamics and challenges encountered by these institutions. Utilizing a mixed-methods approach encompassing interviews, surveys, and comprehensive financial analysis, the research endeavors to gain a deep understanding of the multifaceted aspects shaping the financial landscape of internationally accredited HEIs. The proposed Financial Planning Model integrates various key components, including revenue diversification strategies, effective cost management techniques, rigorous risk assessment methodologies, and proactive stakeholder engagement initiatives. By aligning with the academic missions and accreditation standards of HEIs, this model aims to foster long-term financial sustainability while maintaining institutional integrity and excellence. By offering actionable insights and practical guidelines, the proposed Financial Planning Model seeks to enhance financial management practices within internationally accredited HEIs. It strives to empower institutional leaders and stakeholders with the tools and frameworks necessary to navigate complex financial landscapes, optimize resource allocation, and ensure institutional resilience in the face of uncertainty. In conclusion, this research represents a significant contribution to the advancement of financial management practices in internationally accredited HEIs. It offers a comprehensive and adaptable framework that can serve as a blueprint for institutions striving to achieve financial sustainability while upholding academic excellence and institutional values in an ever-changing global landscape.